Pancasila Sebagai Alternatif Solusi Ideologi Era Postmodern - Sihombing, Edy Syahputra; David Michael Setyadarma (Universitas Katolik Parahyangan, 2024)
The postmodern era, as described by Jean-François Lyotard, is characterized by a deep paradigm of relativism, where truth and values are seen not as absolute but contingent upon perspectives and contexts. After World War II, the world was divided into two major ideological forces, Liberalism and Communism, which competed in the Cold War for global dominance. Although, after the Cold War, Liberalism was deemed relevant to the post-conflict world, various debates indicate that this ideology is not fully capable of addressing the challenges posed by relativism in the postmodern era. In this context, this study employs a qualitative approach with a literature review method to explore the relevance of Pancasila as an alternative solution to the complexities of postmodern relativism. The author argues that Pancasila, with its inclusive and universal values, offers an ideology that can provide stability and integration in a society that is increasingly plural and fragmented.